Про ефективнi термоелектроннi катоди - Lushkin, O. Ye. (Publishing house "Academperiodika", 2019)
A review of scientific works devoted to the most efficient modern thermionic cathodes – oxide cathodes and dispenser cathodes – is made. The main attention is focused on the analysis of emission mechanisms from those electron sources. In addition, the relation between the emission of dispenser cathodes and their physical and technical parameters is considered. The influence of fabrication methods on the cathode performance is discussed.